EFEKTIFITAS MEDIASI DALAM PENYELESAIAN SENGKETA KONSUMEN PADA BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA BUKITTINGGI TAHUN 2014-2017 - Bustamar Bustamar (Institut Agama Islam Negeri Batusangkar, 2017)
Mediation in the settlement of consumer disputes at BPSK Bukittinggi Year 2014-2017 run effectively. 18 of the 33 cases registered inthe Bukittinggi BPSKfrom 2014 to July 2017 were settled by means of mediation, with the remaining 15 cases settled by arbitration. The effectiveness of such mediation is supported by Law no. 8 in 1999 and Kemendag no. 350 / MPP / Kep / 12/2001 which despite the perceived many weaknesses and need improvement, but with the presence of 9 members of the Bukittinggi BPSK assembly which majority of law educated and 3 of them are certified mediators and the existence of adequate facilities can be a counterweight and reinforcement mediation process as well as driving the legal culture of the parties to the dispute.